Risk factors for readmission among a cohort of psychiatric inpatients in Lilongwe, Malawi - Barnett, Brian S. (Int J Psychiatry Clin Pract, 2019)
OBJECTIVES: Inpatient psychiatric capacity is limited in Malawi and no published studies have assessed psychiatric readmissions there. Information about factors associated with readmission may help guide strategies to reduce readmission rates and keep patients stabilized in the community. Our goal was to determine factors associated with readmission among a cohort of psychiatric inpatients in Lilongwe, Malawi. METHODS: We conducted a retrospective chart review of all patients admitted to an inpatient psychiatric unit in Lilongwe, Malawi from January 1 to December 31, 2011. We used logistic regression to test for associations between readmissions during the study period and patient variables. RESULTS: 419 patients were hospitalized during the study period. 29 patients (6.9%) were readmitted at least once during the study period. Readmission was associated only with intentional medication non-adherence at home (aOR: 3.33, p=0.02). CONCLUSIONS: Intentional medication non-adherence is a potentially modifiable behavioral associated with psychiatric readmission. Efforts to improve medication adherence among patients following hospital discharge may help decrease the risk of readmission.